2011
DOI: 10.1038/embor.2011.171
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of α1‐antitrypsin deficiency revealed by the structure of a domain‐swapped trimer

Abstract: a 1 -Antitrypsin (a1AT) deficiency is a disease with multiple manifestations, including cirrhosis and emphysema, caused by the accumulation of stable polymers of mutant protein in the endoplasmic reticulum of hepatocytes. However, the molecular basis of misfolding and polymerization remain unknown. We produced and crystallized a trimeric form of a1AT that is recognized by an antibody specific for the pathological polymer. Unexpectedly, this structure reveals a polymeric linkage mediated by domain swapping the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
217
4
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(233 citation statements)
references
References 24 publications
11
217
4
1
Order By: Relevance
“…It was suggested there that formation of the dimer occurred from an intermediate on the normal folding pathway, which implied that s5A must be the last element of the metastable conformation to form as, by microscopic reversibility, it would be the element most easily removed. Our present results and more recent results from the same group (14) are not consistent with this. s1C inserts Next Followed by s4B and s5B-We next sought to determine whether there was further sequential association within the remaining C-terminal elements.…”
Section: Folding Pathwaycontrasting
confidence: 56%
“…It was suggested there that formation of the dimer occurred from an intermediate on the normal folding pathway, which implied that s5A must be the last element of the metastable conformation to form as, by microscopic reversibility, it would be the element most easily removed. Our present results and more recent results from the same group (14) are not consistent with this. s1C inserts Next Followed by s4B and s5B-We next sought to determine whether there was further sequential association within the remaining C-terminal elements.…”
Section: Folding Pathwaycontrasting
confidence: 56%
“…10 More recently, a structure of a domain-swapped trimer of a1AT was resolved including strand 1 from b-sheet C and Strands 4 and 5 from b-sheet B. 12 In serpins, the amino acid sequence of RCL, within the C-terminus loop, is responsible, for the specificity of protease inhibition. It was also shown that the length of the serpin RCL is critical for its mechanism of protease inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the mutant Z, the substitution E342K in the 5A b-strand prevents the interaction of this strand with the 6A b-strand and the incorporation of this segment into the bsheet A does not take place. 8,11 Moreover, in a recent study, Yamasaki et al 12 produced and crystallized a trimeric form of a1AT recognized by an antibody specific for the pathological polymers. This structure reveals another polymeric state mediated by domain swapping the carboxy-terminal 34 residues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.2c ). Additional models for AAT polymerization have also been proposed based on the crystal structures of a dimer of a serpin antithrombin [ 69 ] and a trimer of a disulfi de mutant of AAT [ 70 ], suggesting that folding trajectories of AAT/Z-AAT could be diverse and likely dynamic, all subject to the local PN.…”
Section: The Folding Stress-responsive Apl In the Liver Of Aatdmentioning
confidence: 99%